THE ROLE OF INNOVATIVE TECHNOLOGIES AND THE CLUSTER APPROACH IN TRAINING MODERN TEACHERS - Abduraxmanov Maqsat Bekjon o‘g‘li (Web of Journals Publishing, 2025)
This article examines the theoretical and practical aspects of developing innovative competence among future teachers within the modern educational system. It explores the integration of the cluster approach into the educational process, the pedagogical effectiveness of innovative technologies, and the importance of creative and critical thinking in teacher training. The study also highlights the role of teachers’ speech culture, personal development clusters, and creative activities in shaping innovative competence.
Keywords: Innovative competence, cluster approach, pedagogical technologies, creative thinking, critical thinking, professional development, speech culture, modern education.